Beneficial effects of elafibranor on NASH in E3L.CETP mice and differences between mice and men - Anita M. van den Hoek (Nature Portfolio, 2021)
Abstract Non-alcoholic steatohepatitis (NASH) is the most rapidly growing liver disease that is nevertheless without approved pharmacological treatment. Despite great effort in developing novel NASH therapeutics, many have failed in clinical trials. This has raised questions on the adequacy of preclinical models. Elafibranor is one of the drugs currently in late stage development which had mixed results for phase 2/interim phase 3 trials. In the current study we investigated the response of elafibranor in APOE*3Leiden.CETP mice, a translational animal model that displays histopathological characteristics of NASH in the context of obesity, insulin resistance and hyperlipidemia. To induce NASH, mice were fed a high fat and cholesterol (HFC) diet for 15 weeks (HFC reference group) or 25 weeks (HFC control group) or the HFC diet supplemented with elafibranor (15 mg/kg/d) from week 15–25 (elafibranor group). The effects on plasma parameters and NASH histopathology were assessed and hepatic transcriptome analysis was used to investigate the underlying pathways affected by elafibranor. Elafibranor treatment significantly reduced steatosis and hepatic inflammation and precluded the progression of fibrosis. The underlying disease pathways of the model were compared with those of NASH patients and illustrated substantial similarity with molecular pathways involved, with 87% recapitulation of human pathways in mice. We compared the response of elafibranor in the mice to the response in human patients and discuss potential pitfalls when translating preclinical results of novel NASH therapeutics to human patients. When taking into account that due to species differences the response to some targets, like PPAR-α, may be overrepresented in animal models, we conclude that elafibranor may be particularly useful to reduce hepatic inflammation and could be a pharmacologically useful agent for human NASH, but probably in combination with other agents.